Quantitative evaluation of slip activity in polycrystalline α-titanium considering non-local interactions between crystal grains. (April 2020) - Kawano, Yoshiki; Sato, Michihiro; Mayama, Tsuyoshi; Mitsuhara, Masatoshi; Yamasaki, Shigeto
Abstract: An indicator to predict the slip operation at the crystal-grain level, namely slip operation factor (SOF), was established as a function of the Schmid factor (SF) and critical resolved shear stress (CRSS). Plastically "soft" and "hard" regions were estimated by the Schmid factor values normalized by the CRSS—the normalized Schmid factor (NSF). The effect of the interaction among the regions was incorporated into SOF. A microstructural map of α-titanium (α-Ti) was obtained by the electron backscatter diffraction patterns. Several spatial distributions of SOF were calculated based on the map by changing the interaction range among the regions. The distributions were compared with those of the strains obtained by the crystal plasticity finite element (CPFE) analysis. Good agreement between the distributions was found near the macroscopic yield point when the interaction range was appropriate, although some significant differences between the distributions were also noticed after the yielding point. The prediction accuracy by SOF was higher than that by SF and NSF. The reasons for the high accuracy revealed by the SOF analysis and the differences between the distributions indicated by the CPFE analysis were also investigated. Highlights: An indicator for slip operation (SOF) was established as a function of Schmid factor. Non-local interactions were taken into account in SOF. Strain distributions of a polycrystalline α-titanium were predicted by SOF. SOF accurately predicted the strain distributions more than normalized Schmid factor.